Quantitative Determination and Toxicity Evaluation of Aristolochic Acid Analogues in Asarum heterotropoides F. Schmidt (Xixin) and Traditional Chinese Patent Medicines - Liu, Suyan; Xian, Zhong; Zhao, Yong; Wang, Lianmei; Tian, Jingzhuo; Pan, Chen; Han, Jiayin; Zhang, Yushi; Li, Chunying; Yi, Yan; Liu, Chenyue; Wang, Dunfang; et al. (Frontiers in Pharmacology, 2021)
Asarum (Xixin), which contains aristolochic acid analogs, is the only specie of genus Aristolochia included in Chinese Pharmacopoeia 2020. But the contents and nephrotoxic effects of aristolochic acid analogs in Asarum (Xixin) and its formulated products are still not clear. An automatic, effective solid phase extraction and UPLC-MS/MS method were established for the pretreatment and quantitative detection of aristolochic acid analogs in commercially available Chinese traditional patent medicines. The cytotoxicity and DNA damages of five aristolochic acid analogs were assessed by CCK8 using human kidney (HK-2) cells and comet assays. HPLC was used to detect the aristolochic acid analogs in Asarum heterotropoides F. Schmidt (Xixin) and results showed the contents of AA I, AA II and AA IIIa were below the detection limit, while AA IVa and AL I were relative high contents of Asarum heterotropoides F. Schmidt (Xixin), within the ranges of 66.50-121.03 μg/g and 19.73-43.75 μg/g, respectively. The contents of aristolochic acid analogs were in the ng/g level in major Chinese traditional patent medicines. AA I and AL I exhibited a relative high cytotoxicity at 48 h in CCK8 assays, while AA II, AA IIIa and AA IVa showed a weak cytotoxicity even at 800-1000 μM. AA I could induce significant pathological changes and direct DNA damage at 40 mg/kg and 20 mg/kg respectively. No distinct nephrotoxicity or hepatotoxicity were observed in AA II, AA IIIa, AA IVa and AL I treated mice at 40 mg/kg in this study. Consumption of Asarum heterotropoides F. Schmidt (Xixin) with confined doses and periods is relative safe as the contents of aristolochic acid analogs in Asarum heterotropoides F. Schmidt (Xixin) and its formulated products are far below the amount that causes acute toxicity in this study. But the long-term toxicity of Asarum heterotropoides F. Schmidt (Xixin) still needs further profound study.